1989
DOI: 10.1111/j.1469-8749.1989.tb03973.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Three Ketogenic Diets in the Treatment of Severe Epilepsy

Abstract: SUMMARY Pre‐ and post‐prandial circulating concentrations of metabolic fuels and plasma insulin are documented in 59 patients with severe epilepsy while receiving either a normal diet, the classical high‐fat ketogenic diet, a medium‐chain triglyceride (MCT) diet, or a modified MCT diet. All three therapeutic diets improved the control of epilepsy and induced a significant increase in the concentrations of blood aceto‐acetate and 3‐hydroxybutyrate, the greatest elevation being seen in patients on the classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…This concurs with the results in healthy adults published by Musa-Veloso et al [12], where the time elapsed after each ketogenic meal revealed a significant negative effect on blood BHB and AA concentrations and that blood ketone bodies are rapidly metabolised for energy. Schwartz et al [24] obtained similar results and advise children with epilepsy to consume more frequent meals and snacks to keep blood ketone concentrations more stable and to avoid the acute rises and falls resulting from ketogenic meals. Some (≈40 %) of our subjects performed no additional physical activities, whereas the others engaged in activities of light to vigorous intensity, factors that may also influence temporary daytime fluctuations in blood and urinary ketones, as muscles consume this energy source rapidly [25].…”
Section: Discussionmentioning
confidence: 83%
“…This concurs with the results in healthy adults published by Musa-Veloso et al [12], where the time elapsed after each ketogenic meal revealed a significant negative effect on blood BHB and AA concentrations and that blood ketone bodies are rapidly metabolised for energy. Schwartz et al [24] obtained similar results and advise children with epilepsy to consume more frequent meals and snacks to keep blood ketone concentrations more stable and to avoid the acute rises and falls resulting from ketogenic meals. Some (≈40 %) of our subjects performed no additional physical activities, whereas the others engaged in activities of light to vigorous intensity, factors that may also influence temporary daytime fluctuations in blood and urinary ketones, as muscles consume this energy source rapidly [25].…”
Section: Discussionmentioning
confidence: 83%
“…It is associated with high mortality rates, low productivity, and cognitive loss 4 . There are a number of reports proving the efficacy of KD that ranges from 30 to 60% in different studies [5][6][7][8][9][10] . our results corroborate previous data, indicating that KD presents higher rates of efficacy than observed with use of several new generations AED 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this diet is easier to prepare and produces greater ketosis (because the fats used, decanoic and octanoic acids, yield more ketones per calorie), it has not been widely accepted because it is associated with bloating and abdominal discomfort. A third variation on the diet, developed at the John Radcliffe Hospital in Oxford, England, represents a combination of the traditional and medium-chain triglyceride diets [8]. Despite some differences in their ability to generate ketones, all three diets have similar efficacy; the Hopkins protocol has been the most widely studied.…”
Section: Clinical Aspects Of the Ketogenic Diet Relevant To Its Mechamentioning
confidence: 99%